The Genus Allium as Poultry Feed Additive: A Review - Kothari, Damini (Animals (Basel), 2019)
SIMPLE SUMMARY: The routine and unregulated use of in-feed antibiotics as growth promoters in poultry have been linked to the development of antimicrobial resistance, a serious global threat to the human, animal, and environment health. Growing public health concerns about food and environmental safety intensified the search for effective antibiotic alternatives in poultry production. The aim of this review is to present the current state of knowledge on the use of alliums as effective poultry feed additives in relation to their effects on growth performance, disease infections, gut and immune modulation, and product quality. ABSTRACT: The genus Allium, belonging to the family Amaryllidaceae has been known since ancient times for their therapeutic potentials. As the number of multi-drug resistant infections has increased due to in-feed antibiotic usage in poultry, the relevance of alliums as feed additives has been critically assessed. Garlic and the other Allium species, such as onions, leek, shallot, scallion, and chives, have been characterized to contain a plethora of bioactive compounds such as organosulfur compounds, polyphenols, saponins, fructans, and fructo-oligosaccharides. Consequently, alliums have been validated to confer antioxidant, antibacterial, antiviral, immunostimulatory, gut homeostasis, and lipid- as well as cholesterol-lowering properties in poultry. This review intends to summarize recent progress on the use of edible alliums as poultry feed additives, their beneficial effects, and the underlying mechanisms of their involvement in poultry nutrition. Perspectives for future research and limitations are also briefly discussed.